Pola Penggunaan Obat Antihipertensi Pada Pasten Geriatri Rawat Jalan di Rumah Sakit TK. II Pelamonia Makassar Pada Bulan Januari-Maret talun 2019 - Desi Reski Fajar; Fardin Fardin; Nur Fadliyah Dyka (Sasambo Journal of Pharmacy, 2020)
Hypertension in the elderly can increase the workload of the heart and arteries which, if continued, can cause damage to the heart and blood vessels. So that requires routine medication adherence to reduce blood pressure. While the elderly with hypertension must take medication regularly because adherence and a good understanding in carrying out therapy can affect blood pressure and prevent complications. This study aims to determine the pattern of the use of hypertension drugs in outpatient geriatric patients in kindergarten hospitals. II Pelamonia Makassar in January-March 2019. This type of research is a non-experimental quantitative study using descriptive design. Descriptive research that aims to make a systematic, factual, and accurate description of the facts and the nature of a particular population or area. This study obtained 23 medical records of geriatric patients who met the inclusion criteria. The inclusion criteria in this study were geriatric patients diagnosed with hypertension with age usia 60 years and receiving hypertension treatment. The results showed that the most commonly used classes of hypertension were amlodipine by 23%, single candesartan by 17%, and micardis by a single 13%, and the most used drug combination therapy was a combination of amlodipine and candesartan by 17%, amlodipine and valsartan by 13%), while candesartan and bisoprolol by 17%.